The Potential of Vegetation Species Diversity for Ecotorourism Development at Nature Reserve of Panjalu Lake - Encep Rachman; Aditya Hani (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2017)
The Nature Reserve of Panjalu Lake is one of the oldest conservation area in Indonesia. As a conservation area, Panjalu Lake has different species of flora that are useful as germplasm conservation, science and education. This study aims to know the potential of vegetation species diversity for ecotourism development at Nature Reserve of Panjalu Lake. The inventory method used is line plot sampling with intensity 15 % in two paths of 500 m (adjusted according length of the area) and 20 m width. Spacing between lines is 200 m and spacing between observation plot is 100 m. Within each path, 50 m x 20 m observation plots were established. The results showed that there are three species of seedlings with highest IVI, namely: Dysoxylum densiflorum Miq. (47.64 %), Calamus zollingerii (47.64 %), and Sterculia macrophylla Vent. (44.37 %). The four species at sapling stage with highest IVI are: Litsea cassiaefolia (114.29 %); Dysoxylum densiflorum Miq (57.14 %); Litsea sp. and Endiandra rubescens Miq (14.29 %). Three species at pole stage with highest IVI, namely: Dysoxylum densiflorum Miq. (143.04%); Litsea cassiaefolia (99.78 %) and Artocarpus elasticus Reinw 9.53 %). Three species at tree stage with highest IVI, namely: Dysoxylum densiflorum Miq (147.924 %), Litsea cassiaefolia (68.753 %), and Eugenia fastigiata Miq ( 31.410 %). Keywords: conservation area, Nature reserve of Panjalu Lake, vegetation structure, Important Value Index